IMPROVING ENGLISH VOCABULARIES THROUGH DERIVATIONAL MORPHEME - Evan Afri; Surya Hendra Putra (Universitas Islam Sumatera Utara (UISU), 2021)
This research aims to improve students' vocabulary acquisition through the strategy of deriving suffixes. The populations of this study are students from Politeknik Ganesha Medan in second semester. This research was conducted through Applied Classroom Action Research (CAR), born in two cycles (cycle 1 and cycle 2), and each process consisted of four meetings. The vocabulary test results showed that the average improvement score of the pre-test was 34.66, the post-test of period 1 was 93.46, and the post-test of period 2 was 97.33. In the first cycle, the nominal comparison rate was 88.83%, the verb nature was 77.46%, the adjective nature was 40.74%, and the adverbial heart was 84.14%. In cycle 2, the nominal comparison rate was 100%, the verb nature was 95.45%, the adjective nature was 65.84%, and the adverbial nature was 94.91%. The proportion of students who passed Minimal Criterion Mastery in each cycle was 100%, cycle 1 increased by 169.64%, and cycle 2 increased by 180.81%. These indicate that there is a significant improvement of the students’ vocabulary mastery through derivational morpheme strategy of the students of Politeknik Ganesha Medan.